Improving human mesenchymal stem cell-derived hepatic cell energy metabolism by manipulating glucose homeostasis and glucocorticoid signaling - Rodrigues, Joana Saraiva; Faria-Pereira, Andreia; Camões, Sérgio Póvoas; Serras, Ana Sofia; Morais, Vanessa Alexandra; Ruas, Jorge Lira; Miranda, Joana Paiva (Frontiers in Endocrinology, 2023)
Introduction The development of reliable hepatic in vitro models may provide insights into disease mechanisms, linking hepatocyte dysmetabolism and related pathologies. However, several of the existing models depend on using high concentrations of hepatocyte differentiation-promoting compounds, namely glucose, insulin, and dexamethasone, which is among the reasons that have hampered their use for modeling metabolism-related diseases. This work focused on modulating glucose homeostasis and glucocorticoid concentration to improve the suitability of a mesenchymal stem-cell (MSC)-derived hepatocyte-like cell (HLC) human model for studying hepatic insulin action and disease modeling. Methods We have investigated the role of insulin, glucose and dexamethasone on mitochondrial function, insulin signaling and carbohydrate metabolism, namely AKT phosphorylation, glycogen storage ability, glycolysis and gluconeogenesis, as well as fatty acid oxidation and bile acid metabolism gene expression in HLCs. In addition, we evaluated cell morphological features, albumin and urea production, the presence of hepatic-specific markers, biotransformation ability and mitochondrial function. Results Using glucose, insulin and dexamethasone levels close to physiological concentrations improved insulin responsiveness in HLCs, as demonstrated by AKT phosphorylation, upregulation of glycolysis and downregulation of Irs2 and gluconeogenesis and fatty acid oxidation pathways. Ammonia detoxification, EROD and UGT activities and sensitivity to paracetamol cytotoxicity were also enhanced under more physiologically relevant conditions. Conclusion HLCs kept under reduced concentrations of glucose, insulin and dexamethasone presented an improved hepatic phenotype and insulin sensitivity demonstrating superior potential as an in vitro platform for modeling energy metabolism-related disorders, namely for the investigation of the insulin signaling pathway.